Reducing free fatty acid in used cooking oil using bagasse adsorbent - Mariam Firdhaus Mad Nordin; Marinah Muhammad; Rizki Wannahari (2012)
The used of bagasse as adsorbent is not common or apparent. This is odd especially for several reasons;(1)the structural component of bagasse which is made up of carbon material is suitable as adsordent, (2)bagasse is in abundance, easily available and not used led to waste issue and (3) adsorbent bagasse futher reduce solid waste disposal and hence reducing one source of environmental pollution.This study was undertaken to explore the possibility of using bagasse as adsorbent. Specially, bagasse is being experimented to reduce the harmful content such as FFA (Free Fatty Acid) in used cooking oil. The variation of adsorbent weight and contact time are used in this research as parameters to determine the effective time and the amount of adsorbent that should be used in the oil refining process. From the experiment conducted, it can be established that bagasse when use as an adsorbent can be reduce FFA to 82.14% which is lower the harmful limit. This result is obatianed when 7.5 gram of bagasse for 60 minutes contact time was used. For isotherm adsorption, isotherm Freundlich has a higher level of linearity than Langmuir. Isotherm Freundlinch is about 99.61% and Langmuir is 98.9% for FFA in contact time variation. For weight variation, the level of linearity Langmuir is 19.67 % which is higher than Freundlinch which only reached by 16.78 % . This result advocates that the Freundlich isotherm mechanism is more suitbale for FFA absorbance levels in contact time variation, while the Langmuir suitable for weight variation